Anti Hoaks Pemilu 2024: Pelatihan Periksa Fakta oleh Pemilih Pemula - Amelia Dwi Handayani; Nurlaili Khikmawati; Aghnia Dian Lestari (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
New voters from Gen Z do not have experience in voicing their aspirations in the General Election (Pemilu). Meanwhile, their political participation is necessary, considering that they are one of the two majority groups of voters in the 2024 elections. On the other hand, these first-time voters from Gen Z have good digital skills, even though they are not yet accompanied by a high level of civility. They are also a group that is vulnerable to being exposed to hoaxes and does not yet have the knowledge and skills to use several digital methods and tools to check the validity of the information they receive.The digital literacy program in this service activity was carried out to increase awareness of the political participation of novice voters (Gen Z) in the 2024 Election and strengthen the digital literacy of novice voters (Gen Z) to carry out fact checking using fact checking tools or applications from Mafindo and Google. The service program is carried out in the form of training and adopts material from the Tular Reasoning Program initiated by Mafindo. The training applies a debunking approach that focuses on fact-finding to counter false information.In its implementation, the training activity involved Class XII students from SMAN 4 and SMAN 7 Cirebon City aged between 17-19 years as participants. They are among Gen Z who are exercising their right to vote for the first time in the 2024 elections. By implementing a debunking approach, they are trained to be critical of the information they receive, so that they do not easily believe or carelessly re-distribute information whose truth is not certain. They are also encouraged to participate in the 2024 elections and are equipped with the knowledge and skills to check the validity of information using fact-checking tools or applications